Thermodynamically consistent entropic-force cosmology - Zamora, Darío Javier (2022)
We analyze the thermodynamical consistency of entropic-force cosmological models. Our analysis is based on a generalized entropy scaling with an arbitrary power of the Hubble radius. The Bekenstein-Hawking entropy, proportional to the area, and the nonadditive Sδ=3/2-entropy, proportional to the volume, are particular cases. One of the points to be solved by entropic-force cosmology for being taken as a serious alternative to mainstream cosmology is to provide a physical principle that points out what entropy and temperature have to be used. We determine the temperature of the universe horizon by requiring that the Legendre structure of thermodynamics is preserved. We compare the performance of thermodynamically consistent entropic-force models with regard to the available supernovae data by providing appropriate constraints for optimizing alternative entropies and temperatures of the Hubble screen. Our results point out that the temperature differs from the Hawking one. The novelty of this work is that our analysis is based on a generalized entropy scaling with an arbitrary power of the Hubble radius, instead of a specific entropy. This allows us to conclude on various models at once, compare them, and conserve the scaling exponent as a parameter to be fitted with observational data, thus providing information about the form of the actual cosmological entropy and temperature. In addition, we point out that some entropic-force cosmological models previously available in the literature are not thermodynamically consistent. We provide here a physical principle which links the horizon temperature and entropy in consistency with thermodynamics.